(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Diabetic foot ulcers (DFUs) pose a significant global health challenge due to its association with high morbidity and mortality rates. These chronic lesions, prevalent among individuals with diabetes mellitus (DM), result from a complex interplay of factors including peripheral neuropathy, peripheral artery disease, trauma, and impaired wound healing. Pseudomonas aeruginosa, a notorious pathogen linked to DFU infections, exhibits inherent resistance mechanisms and biofilm formation capabilities, complicating treatment strategies. This study aimed to assess the occurrence of CTX-M and qnrA genes among ESBL-producing P. aeruginosa isolates from DFUs patients at Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH) in Bauchi, Nigeria. From 150 collected samples, P. aeruginosa was the most frequently isolated organism (37 isolates). Antimicrobial susceptibility testing revealed significant resistance to cephalosporins and fluoroquinolones, with 46.7% of isolates exhibiting ESBL production. Molecular analysis identified the presence of CTX-M genes in three ESBL-producing isolates while qnrA genes were not detected, the absence of qnrA suggests a lack of plasmid-mediated quinolone resistance in the isolates. Clinically, this finding could imply that quinolone-based treatment may still effective against infection. These findings underscore the urgent need for antimicrobial stewardship and tailored treatment strategies to address multidrug-resistant P. aeruginosa infections in DFU patients, emphasizing the importance of molecular surveillance to inform targeted interventions and improve patient outcomes.